2021
DOI: 10.3390/pharmaceutics13060778
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Modelling of Cabozantinib to Simulate Enterohepatic Recirculation, Drug–Drug Interaction with Rifampin and Liver Impairment

Abstract: Cabozantinib (CAB) is a receptor tyrosine kinase inhibitor approved for the treatment of several cancer types. Enterohepatic recirculation (EHC) of the substance is assumed but has not been further investigated yet. CAB is mainly metabolized via CYP3A4 and is susceptible for drug–drug interactions (DDI). The goal of this work was to develop a physiologically based pharmacokinetic (PBPK) model to investigate EHC, to simulate DDI with Rifampin and to simulate subjects with hepatic impairment. The model was estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…Currently, these parameter changes have been applied to multiple PBPK models (see Supplementary Table S4 ). However, most published papers for PBPK models of hepatic impairment have not taken into account absorption changes between impaired and normal hepatic function ( Morcos et al, 2018 ; Gerner and Scherf-Clavel, 2021 ; Fan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, these parameter changes have been applied to multiple PBPK models (see Supplementary Table S4 ). However, most published papers for PBPK models of hepatic impairment have not taken into account absorption changes between impaired and normal hepatic function ( Morcos et al, 2018 ; Gerner and Scherf-Clavel, 2021 ; Fan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this simulation, the used physiological parameters in patients with hepatic impairment were taken from the published papers ( Heimbach et al, 2021 ; Willmann et al, 2021 ). The plasma protein scale factor (PPSF) in PK-Sim ® was modified to describe changes in plasma albumin protein concentration and unbound PAZ fraction ( Gerner and Scherf-Clavel, 2021 ). Based on the following equation derived from the paper ( Johnson et al, 2010 ), PPSF was estimated.…”
Section: Methodsmentioning
confidence: 99%
“…In current clinical practice, the CZ tablet formulation (Cabometyx™) was approved at a dose of 60 mg daily for treating advanced RCC. CZ at 2–2.5 mg/kg per day is equivalent to 15–20 mg per day in humans [ 67 , 73 ], and previous preclinical in vivo studies using oral CZ monotherapy (once daily oral gavage of 10–60 mg/kg CZ) have demonstrated its anticancer effects in mouse models of various tumor types, including RCC Renca cell lines [ 41 , 67 ]. For example, a recent study using the subcutaneous Renca model demonstrated the CZ (10 mg/kg, once per day by gavage for 14 days)-mediated tumor growth inhibition through triggered infiltration of both antineoplastic neutrophils/T cells into the tumor bed and significantly enhanced the cytotoxicity of tumor-infiltrated T cells [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there was still an overestimation in schaftoside plasma concentration especially for C max . According to the literature, intestinal absorption may be limited by solubility, thus imposing an upper limit on the absorption of compounds ( Gerner and Scherf-Clavel, 2021 ). Even so, the predicted C max and AUC 0-t values of schaftoside after oral administration of TFDS in rats were within ∼1.5-fold of the observed values, which met the acceptance criteria (<2-fold).…”
Section: Discussionmentioning
confidence: 99%
“…There are some limitations to this study. One limitation which might reduce the applicability of the model was the lack of iv data of schaftoside in human ( Gerner and Scherf-Clavel, 2021 ). Although the rat PBPK model utilized the iv and oral plasma concentration-time profiles of schaftoside and TFDS, the establishment of human PBPK model only based on the oral data of schaftoside after oral administration of TFDS.…”
Section: Discussionmentioning
confidence: 99%